In Praise of the Stepmother — cohesion and coherence between texts and textiles - Pajuelo Lara, Katherine (2023)
Mario Vargas Llosa’s erotic novel In Praise of the Stepmother (1998) has fourteen chapters and one epilogue — six of them are introduced by a classic piece of art (four are canvas from 15th to 16th centuries, and two from 20th century). However, images are not there to be a visual aid to understand the plot but to be a part of it, in other words, the real characters’ experiences are reflected in the paintings. The real characters prolong their erotic phantasy in the paintings, and breathe life into the characters painted. Under the concepts of cohesion and coherence from text linguistics, we explain that text and textile (canvas) in the novel are linked together and form a coherent plot.